Cómo tratar con personas difíciles y problemáticas - Hasson, Gill (BookaVivo, 2021)
DON'T LET PEOPLE WITH PROBLEMS GET TO YOU! Whether it's a manager who keeps moving the goal posts, an uncooperative colleague, a negative friend, or a critical family member, some people are just plain hard to get along with. Often their immediate response is to cringe or get angry, become defensive or attack. But there are smarter moves to make when dealing with difficult people. This book explains how to deal with a series of situations with difficult people and focus on what can be changed. This book will help you: -Understand what makes difficult people tick and how best to handle them -Learn ways to confidently confront others and resist the urge to attack again -Develop strategies for calmly navigating stress-laden situations emotions -Dealing with all kinds of difficult people - hostile, manipulative and the impossible -Know when to pick your battles, and when to walk away Why let someone else's bad attitude ruin your day? How to Deal With Difficult People arms you with all the tools and tactics you need to handle all kinds of people, to make your life less stressful and much easier.